Unwinding Ariadne's identity thread: Privacy risks with fitness trackers and online social networks - Aktypi, A; Nurse, J; Goldsmith, M (Association for Computing Machinery, 2017)
The recent expansion of Internet of Things (IoT) and the growing trends towards a healthier lifestyle, have been followed by a proliferation in the use of fitness-trackers in our daily life. These wearable IoT devices combined with the extensive use by individuals of Online Social Networks (OSNs) have raised many security and privacy concerns. Individuals enrich the content of their online posts with their physical performance and attendance at sporting events, without considering the plausible risks that this may result in. This paper aims to examine the potential exposure of users' identity that is caused by information that they share online and personal data that are stored by their fitness-trackers. We approach the privacy concerns that arise by building an interactive tool. This tool models online information shared by individuals and elaborates on how they might be exposed to the unwanted leakage of further personal data. The tool also illustrates the privacy risks that arise from information that people expose, which could be exploited by malicious parties such as fraudsters, stalkers and other online and offline criminals. To understand the level of users' awareness concerning their identity exposure when engaging with such devices and online services, we also have conducted a qualitative analysis and present our findings here.